2009
DOI: 10.1556/avet.57.2009.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin treatment on follicular development and oocyte quality in Chios ewes — Short communication

Abstract: Follicular development and oocyte quality were assessed by laparoscopic observation and in vitro fertilisation, respectively, in melatonin-treated (Group M) and control (Group C) anoestrous Chios ewes (n = 10 in each group). Fourteen days after melatonin insertion, all ewes had laparoscopic evaluation of the follicular population followed by oocyte pick-up (OPU); on day 22 intravaginal progestagen sponges were inserted for 14 days. Two days after sponge removal the follicular population was re-evaluated and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
(21 reference statements)
0
7
0
1
Order By: Relevance
“…Additionally, melatonin promotes follicular development by increasing production of insulin-like growth factor I which stimulates mitogenic growth of cumulus cells [ 38 ]. Although previous in vivo studies demonstrated exogenous FSH may mask effects of melatonin on follicular development, exogenous melatonin tended to increase the number of developing follicles [ 39 ]. Perhaps the role of melatonin in regulation of germ cell development is species- or age-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, melatonin promotes follicular development by increasing production of insulin-like growth factor I which stimulates mitogenic growth of cumulus cells [ 38 ]. Although previous in vivo studies demonstrated exogenous FSH may mask effects of melatonin on follicular development, exogenous melatonin tended to increase the number of developing follicles [ 39 ]. Perhaps the role of melatonin in regulation of germ cell development is species- or age-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin can be used alone, or combined with other hormonal treatments, after an artificial light (photoperiodic) treatment. In several studies concerning ewes of different breeds, melatonin administration has been found to advance the onset of reproductive activity (Arendt et al, 1983;Karsch et al, 1984;English et al, 1986); furthermore, melatonintreated ewes appeared to have better oocyte quality and higher ovulation and conception rates (Stellflug et al, 1988;Kouimtzis et al, 1989;Tsiligianni et al, 2009).…”
mentioning
confidence: 98%
“…Its stimulate ovarian steroidogenic gene expression (95) and luteinisation of graffian follicle (96). During the anoestrous period, MLT regulate a follicular growth (have a strong role in regulation and development) and oocyte efficiency (97). Exogenous MLT conserve cumulus cells from DNA damage during In vitro maturation (IVM) (98) (99), and the MLT supplementation to the IVM and culture medium can reduced Reactive oxygen species (ROS) (antioxidant effect) and get better competence of oocytes, which led to rise the quality and quantity blastocyst proportions and improve the embryos quality.…”
Section: The Use Of Mlt In Reproductive Techniquesmentioning
confidence: 99%